The Views of Greek Educators on Evaluation Techniques: The Case of Model Experimental Schools - Î‘nastasia Papadopoulou (Journal of General Education and Humanities, 2023)
The term "evaluation of the educational work" and, respectively, of the teachers was established in our country during the post-colonial period. The following questions particularly concerned both the educational community and the state in general: "How are or should the results of the evaluation be used?", "Can all aspects of the work produced at the school unit level and the effects of teachers on their students be objectively measured and evaluated?", "How can the subjective element be reduced in the procedure of teacher evaluation?", "Is it possible to apply uniform evaluation criteria to schools that operate in heterogeneous socio-economic, cultural, or geographical environments?", "What is the role of the teachers and the Management of each school and school counselor as well as other actors of the school community (students, parents, other staff)?" The answer to the above questions comes through the research carried out on 405 teachers in Greece and highlights various philosophical, political, and pedagogical dimensions concerning the purpose of Evaluation, the bodies, forms, techniques, and evaluation criteria.